2019
DOI: 10.3390/nu11051081
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of MAPK Signaling in NSC-34 Motor Neurons Treated with Vitamin E

Abstract: Vitamin E family is composed of different tocopherols and tocotrienols that are well-known as antioxidants but that exert also non-antioxidant effects. Oxidative stress may be involved in the progression of neurodegenerative disorders including amyotrophic lateral sclerosis (ALS), characterized by motor neuron death. The aim of the study was the evaluation of the changes induced in the transcriptional profile of NSC-34 motor neurons treated with α-tocopherol. In particular, cells were treated for 24 h with 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This study also concluded that VitE significantly improved motor functioning in ALS patients [305]. In a study focusing on transcriptional profiles, VitE prevented the death of NSC-34 motor neurons in ALS through the downregulation of the c-Jun N-terminal kinase (JNK) and p38 MAPK pathway (cell death), and upregulation of the extracellular signal-regulated kinase (ERK) pathways (cell survival) [306].…”
Section: Vitamins In Amyotrophic Lateral Sclerosismentioning
confidence: 80%
“…This study also concluded that VitE significantly improved motor functioning in ALS patients [305]. In a study focusing on transcriptional profiles, VitE prevented the death of NSC-34 motor neurons in ALS through the downregulation of the c-Jun N-terminal kinase (JNK) and p38 MAPK pathway (cell death), and upregulation of the extracellular signal-regulated kinase (ERK) pathways (cell survival) [306].…”
Section: Vitamins In Amyotrophic Lateral Sclerosismentioning
confidence: 80%
“…α-tocopherol is the main form of vitamin E in tissues and is known to be an effective natural scavenger of reactive oxygen species [31] . A study evaluated the changes induced in the transcriptional pro le of NSC-34 motor neurons treated with α-tocopherol and found that α-tocopherol may be an e cacious therapy in preventing motor neuron death [32] . A previous study also suggested that tocopherol derivatives can reduce muscle atrophy and improve survival in SOD1 G86R mouse models by protecting against oxidative and DNA damage-induced stresses [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activities of vitamin E have been linked to pain management therapy and are actively linked to the pain signaling pathway (15,16). Hence, using in-vivo animal models with breast cancer-induced bone pain might postulate the roles of vitamin E supplementation in managing pain caused by cancer.…”
Section: Introductionmentioning
confidence: 99%